2017
DOI: 10.17221/23/2015-pps
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of certain common ferns against red spider mite Oligonychus coffeae and tea mosquito bug Helopeltis theivora infesting tea

Abstract: Prabhakaran P., Radhakrishnan B., Srikumar K.K., Suresh Kumar B. (2017): Efficacy of certain common ferns against red spider mite Oligonychus coffeae and tea mosquito bug Helopeltis theivora infesting tea. Plant Protect Sci., 53: 232-242.In search for botanicals as an alternative remedy to synthetic chemicals in the pest control of tea plantations, ferns such as adiantum raddianum, asplenium aethiopicum, Cyclosorus interruptus, dicranopteris linearis, diplazium polypodioides, and Pteridium aquilinum were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
1
2
0
1
Order By: Relevance
“…The discovery of insecticidal proteins with new modes of action (MOA) or sites of action (SOA) is another approach to overcome resistance. Recently, two novel insecticidal proteins, Tma12 and IPD083, have been isolated from fern species supporting earlier observations that ferns are inherently resistant to insect infestation ( 15 17 ). Tma12 is a chitin-binding protein from the family of AA10 monooxygenases that are normally bacterial enzymes.…”
supporting
confidence: 70%
“…The discovery of insecticidal proteins with new modes of action (MOA) or sites of action (SOA) is another approach to overcome resistance. Recently, two novel insecticidal proteins, Tma12 and IPD083, have been isolated from fern species supporting earlier observations that ferns are inherently resistant to insect infestation ( 15 17 ). Tma12 is a chitin-binding protein from the family of AA10 monooxygenases that are normally bacterial enzymes.…”
supporting
confidence: 70%
“…Both adults and nymphs of H . theivora take in the plant juice from young buds, leaves, fruits and shoots with their piercing-sucking mouthparts 25 . As a consequence, drying up of shoots and fruits can arise from their sucking behavior, which causes more than 25% of crop losses 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other studies indicated that B. antidysenterica is highly efective against mosquito larvae [41]. Te aqueous tinctures of ferns showed acaricidal and insecticidal activity depending on the exposure time and concentration [42], and C. macrostachyus had molluskicidal activity [41].…”
Section: Discussionmentioning
confidence: 79%